CONCRETE MIX DESIGN - Dr. S. K.Dubey; Prof. P. R. Hedgire; Prof. V. M. Bhogade (International Journal of Innovations in Engineering Research and Technology, 2021)
The compressive strength of hardened concrete which is generally considered to be an index of its other properties, depends upon many factors, e.g. quality and quantity of cement, water and aggregates; batching and mixing; placing, compaction and curing.The requirements which form the basis of selection and proportioning of mix ingredients are : a)The minimum compressive strength required from structural considerationb)Theadequate workability necessary for full compaction with the compacting equipment available.c) Maximum water-cement ratioand/or maximum cement content to give adequate durability for the particular site conditions